If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18x + 6x + -36x + 12 = 0 Reorder the terms: 12 + -18x + 6x + -36x = 0 Combine like terms: -18x + 6x = -12x 12 + -12x + -36x = 0 Combine like terms: -12x + -36x = -48x 12 + -48x = 0 Solving 12 + -48x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -48x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -48x = 0 + -12 -48x = 0 + -12 Combine like terms: 0 + -12 = -12 -48x = -12 Divide each side by '-48'. x = 0.25 Simplifying x = 0.25
| 1/6(5x-9)=3 | | 19-h-h=18 | | 50k+100=40k+100 | | 9(3x+2)=12x+8 | | -97-24+130= | | 1/5x+2=16 | | 1.8/0.09 | | 8+n=100 | | 8-n=100 | | 3X+12-4=20 | | 81-9v^2=0 | | (3/4x+6)(-3x+1/2)=0 | | x*5+52=x*8-14 | | y+11=10/11(x-1) | | 8x-15=4+2x | | 7-7x=97-28x | | 6z-5z=7-20 | | 2v*4y^8*3v^5y^6= | | 1-11/2n=100 | | 12x^5y^3*2xy= | | 2x+14=-63-9x | | 5=3(x-0) | | 3(4x+3)(2x-5)=0 | | d-4(d+8)=-8 | | 3(4x-3)(2x-5)=0 | | 8/x=7/x-2 | | 35Q^2+33q+4=0 | | 13(x-9)=7x-10 | | 139=x+2x+(x+15) | | 11(x-2)=7x-11 | | 12x+13=7x+20 | | 32=x+x+(x+2)+(x+2) |